2018
DOI: 10.3389/fnut.2018.00079
|View full text |Cite
|
Sign up to set email alerts
|

Feed Choice Led to Higher Protein Intake in Broiler Chickens Experimentally Infected With Campylobacter jejuni

Abstract: In 2016, Campylobacter was the most commonly reported gastrointestinal bacterial pathogen in humans in the European Union with 246,307 reported cases. Of these cases, 83.6% were Campylobacter jejuni. The objective of the present study was to investigate to what extent an infection with C. jejuni alters the feed intake behavior of broiler chicks in terms of protein intake. This was done to see if, conversely, measures of control could be derived. In total, 300 commercial broilers of the Ross 308 line were alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The results of these studies are all similar to ours, in which dietary supplementation with 1000 and 2000 mg/kg GCP improved ADG and FCR in weaned piglets compare with non‐supplemented controls. FCR reflected feed consumption per kilogram of body weight gain (Visscher et al, 2018). Therefore, the decrease of FCR and the increase of ADG indicated that the growth performance of piglets was improved.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies are all similar to ours, in which dietary supplementation with 1000 and 2000 mg/kg GCP improved ADG and FCR in weaned piglets compare with non‐supplemented controls. FCR reflected feed consumption per kilogram of body weight gain (Visscher et al, 2018). Therefore, the decrease of FCR and the increase of ADG indicated that the growth performance of piglets was improved.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important differences between broiler and layer breeds, which affect both natural and administered intestinal microfloras is the composition and the amount of feed ingested. The considerably higher proportion of protein in the broiler diet [36] compared to layers may result in a different composition of the intestinal flora. For instance, it was shown that the dietary protein content affected diversity and population number of microbiota resulting in a modulation of the Campylobacter jejuni pathogenesis in broilers [37].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was shown that the dietary protein content affected diversity and population number of microbiota resulting in a modulation of the Campylobacter jejuni pathogenesis in broilers [37]. A higher protein content in feed was associated with a higher caecal Campylobacter jejuni load [38], therefore, reducing the availability of protein could limit the spread of infection [36]. Infection studies between broiler-and layer-type chickens [37] provided evidence that the colonisation pattern of commensal bacteria may depend on the breed and/ or the corresponding diet.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that this increase may have been because of the higher crude protein in the self-made feeds compared to the commercial feed rather than the nature of the protein source itself [322]. A third study from the same group found that providing broilers with a choice of a high or low protein feed from day 14 of age did not provide protection against C.jejuni colonisation relative to a conventional diet, but interestingly, C.jejuni challenge did increase the consumption of the high protein diet compared to the unchallenged birds [323].…”
Section: Substitute Feed Componentsmentioning
confidence: 99%